2019
DOI: 10.1002/htj.21558
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of single‐flow solar air collectors with different configurations of absorber plates

Abstract: In the current study, an experimental analysis of exergy performance for different absorber plates is done. Three types of absorber plates are supplied with different fin arrangements with a variable air mass flow rate. The exergy analysis to evaluate the exergy performance of the solar air heaters uses experimental data for conventional and finned solar air collectors with different arrangements of fins. The main aim of the current study is to compare the exergy performance of the conventional solar air colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The factors concerned with geographical location are the fraction of absorbed energy, the solar intensity, and the ambient weather conditions. The behavior of the exergy efficiency shown in Figures 11 and 12 is comparable only with the work conducted by Khalil et al 28 Table 2 presents representative studies of exergy efficiency for SAH with fins that used in different applications. When a comparison in terms of exergetic efficiency is held between the present work and the literature, it can be observed that exergetic efficiency values are accepted.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The factors concerned with geographical location are the fraction of absorbed energy, the solar intensity, and the ambient weather conditions. The behavior of the exergy efficiency shown in Figures 11 and 12 is comparable only with the work conducted by Khalil et al 28 Table 2 presents representative studies of exergy efficiency for SAH with fins that used in different applications. When a comparison in terms of exergetic efficiency is held between the present work and the literature, it can be observed that exergetic efficiency values are accepted.…”
Section: Resultssupporting
confidence: 77%
“…In addition, a large amount of the exergy annihilation can be avoided in the glass cover. Experimental tests for an SAH with different fin arrangements on the absorber plate were conducted by Khalil et al 28 to evaluate exergetic performance. They found that an inclined staggered fin arrangement gives a higher value of exergy efficiency of around 77%.…”
Section: Introductionmentioning
confidence: 99%
“…For each measured variable, one or more elemental uncertainties can contribute to the total uncertainties for the variable. These elemental uncertainties were combined using the Root Mean Squared (RMS) rate method according to [20] and [21]. For the measured variables in the different experiments, the results for the elemental uncertainties are summarized in Table 2 & Table 3.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Khalil et al [11] studied the different arrangements of turbulators in SAH and showed the highest exergy efficiency for inclined staggered turbulators. Das et al [12] were compared the plain absorber with a sand coated absorbing surface of a SAH.…”
Section: Introductionmentioning
confidence: 99%